Pertumbuhan dan Hasil Biji Genotipe Kedelai di Berbagai Intensitas Naungan - Sundari, Titik; Anggoro Susanto, Gatut Wahyu (Jurnal Penelitian Pertanian Tanaman Pangan, 2015)
Intensity and quality of sunlight received by plants during the reproductive period greatly influence the soybean yield and yield components. Growth and seed yield of soybean genotypes at different shade intensities were assessed through research conducted at the Research Station of Kendalpayak, Malang, in the year 2011. Three soybean varieties, namely: Pangrango, Argomulyo, and Grobogan, and twelve soybean promising lines tolerant to shade were tested on four artificial shade intensities, ie without shade (N0), shade of 25% (N1), 50% (N2), and 75% (N3). Placement of treatments in each level of shade was arranged in a randomized block design, replicated three times. Results showed that: shade treatment changed the microclimate under the shading. Shade treatment of 25%, 50%, and 75% caused different stress intensities. Shade intensity of 75% caused an increase in plant height and specific leaf area, a reduction in the number of leaves and leaf area, photosynthetically active radiation (PAR) absorption rate, photosynthetic rate, leaf chlorophyll index, number of filled pods, and seed weight per plant. Number of filled pods was considered effective to be used as a basis for selecting soybean genotypes having high yield in shaded conditions. Plant height and seed weight could be used as an indicator for soybean shade tolerance. Genotype AI26-1114-8-28 and IIj9-299-1-4 were considered as shade-tolerant up to 75% shade based on the stress index tolerance value (ITC).